The effects of 1,25 D3 on the mouse osteopontin promoter - Strasburg, Annalyse (My University, 2007)
Vitamin D (1,25 D3) is an important transcriptional regulator of many genes including our gene of interest, osteopontin. Osteopontin is a known regulator of bone calcification and mineralization and is involved in signaling in the immune response. We looked at osteopontin expression in mouse MC3T3-El preosteoblast cells in response to 1,25 D3. We also tested how pathways known to crosstalk with 1,25 D3 modify mOPN expression. These include MNAR, Wnt3a conditioned media, PTH, and dexamethasone. Additionally, we checked how ZK159222, an antagonist to VDR with partial agonist activity, effects mOPN expression. The osteopontin promoter was cloned into a POL3 reporter vector and transfected into MC3T3-El cells. A luciferase assay normalized by a tl-gal assay was used to measure gene expression. 1,25 D3 induces activity of the mOPN promoter. ZK159222, MNAR, Wnt3a conditioned media, PTH, and dexamethasone were not found to effect mOPN promoter activity in the presence of 1,25 D3.
15 p.
Keywords: Biology; Biochemistry